Enhancing Rural Women's Technical and Vocational Capability through Homestay Initiatives in Nepal: An Ethnographic Exploration (Journal of Training and Development, 2025)
'Homestay tourism' occupies significant space in Nepal's tourism sector, and these homestays are mostly operated by women, who are often informally educated and have less access to modern skills and knowledge-gaining opportunities. However, limited information is available on rural women's experiences in such endeavors. This paper elaborates the experiences of rural women who received various types of technical and vocational training in the process of developing and managing community homestays in rural areas of Nepal. The study was carried out using qualitative approach (ethnography) in the Mahabharat Hills of Bagmati Province administering various qualitative tools, such as participant observations, 'bhalakusari' (intimate informal talks/'kurakani'), focus group discussions (FGDs), and study of local artifacts. A total of seven homestay operators (women) were engaged in the close observations and 'bhalakusari'. Additional reflections were also gathered from other stakeholders: the family members, tourists, local leaders, as well as the community facilitators. The findings suggest that homestay tourism in the area has been playing significant role in the process of transferring technical knowledge and vocational skills to these rural women, so that they are inspired and motivated to engage in the homestay enterprising with better confidence. The study also concludes that homestay operators' limited educational and literacy skills, and less exposures have put difficulties in the learning and capacity development processes. Suitable training courses with local and/or simple Nepali language, along with adequate reading/ supporting materials and continued facilitation and backstopping are some of the practical implications suggested by the study.